Directed SN2 Glycosylation Employing an Amide-Functionalized 1‑Naphthoate Platform Featuring a Selectivity-Safeguarding Mechanism - Ma, Xu; Zhang, Yongliang; Zhu, Xijun; Wei, Yongliang; Zhang, Liming (Journal of the American Chemical Society, 2023)
This work implements a catalytic SN2 glycosylation by employing an amide-functionalized 1-naphthoate platform as a latent glycosyl leaving group. Upon gold-catalyzed activation, the amide group enables the SN2 process by directing the attack of the glycosyl acceptor via H-bonding interaction, which results in stereoinversion at the anomeric center. Unique in this approach is that the amide group also enables a novel safeguarding mechanism by trapping oxocarbenium intermediates and, hence, minimizing stereorandom SN1 processes. The strategy is applicable to the synthesis of a broad range of glycosides with high to excellent levels of stereoinversion from anomerically pure/enriched glycosyl donors. These reactions are generally high-yielding, and their applications in the synthesis of challenging 1,2-cis-linkage-rich oligosaccharides are demonstrated.